THE YUDOMA GROUP OF STRATOTYPE AREA: C-ISOTOPE CHEMOSTRATIGRAPHIC CORRELATIONS AND YUDOMIAN-VENDIAN RELATION - Semikhatov M.A.; Kuznetsov A.B.; Podkovyrov V.N.; Bartley J.K.; Davydov Yu.V. (My University, 2004)
Representative C-isotope characteristics are first obtained for the Lower Yudomian carbonates (YuKanda Formation) from the Belaya and Sakhara sections in the Yudomian stratotype area. The least altered carbonate samples that elucidate further C-isotope chemostratigraphy of formerly studied Upper Yudomian interval were selected based on strict geochemical criteria (Mn/Sr ≤ 4, Fe/Sr ≤ 10.0, δ 18O > -10‰ in limestones and Mn/Sr ≤ 6. Fe /Sr <15δ18O > -10‰ in dolostones). In the studied samples, δ13C values demonstrate the in-phase variations of comparable amplitude at the correlative levels of both sections. They are used to plot the generalized curve of δ 13C variations in the Lower Yudomian succession that is divisible, based on respective trends, into intervals corresponding to three subformations of the Yukanda Formation. Characteristic of the Yalan Subformation, the lower one, are prevailing high positive δ 13C values. In the Mal Subformation (middle one), this parameter declines down to moderate positive values with two short negative excursions complicating the general trend. Low negative δ 13C values are typical of the Tokur Subformation that is upper in the succession. By means of C-isotope chemostratigraphy, biostratigraphy and isotopic-geochronological data, the Yudomian type sections are correlated with terminal Precambrian successions of North Siberia, Namibia, and Oman, and the resulting inferences are as follows. (1) The pre-Nemakit-Daldynian intervals of Vendian successions in Siberia are compatible in their C-isotope characteristics with the reference chemostratigraphic curve (Saylor et al., 1998) and add to it from below the interval with high positive δ13C values, the lower boundary of which is at the level of inversion from positive to negative values in the cap carbonates of the lower Varangerian tillites. (2) In the stratotype area, the Lower and Upper Yudomian deposits are separated by the regional hiatus (time span of 4 to 4.5 m.y.). (3) Judging from δ13C values, basal horizons of Yudomian carbonates are stratigraphically higher than the cap dolomites of the lower Varangerian tillites, and consequently the Yudomian carbonate succession is less than Vendian in stratigraphic range. (4) The direct evidence of age relation between the Vendian and basal Yudomian terrigenous deposits is unknown, but indirect considerations suggest that the latter accumulated during the Early Vendian deglaciation. (5) Negative excursions of δ13C values, which are recorded in the Mal Formation of Uchur-Maya region and near the Kufai Formation top in Oman, presumably reflect events related to the late Varangerian glaciation.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский